Population genetics of Colletotrichum truncatum associated with soybean anthracnose - Rogério, Flávia (2019)
The soybean crop is one of the main agricultural crops, with high global economic relevance. The large area under soybean cultivation in Brazil, including the incorporation of new areas in the northern and midwestern regions, mostly under monoculture and non-tillage system, has been affected the prevalence and the intensity of diseases. Among these, one of most prominent is anthracnose, mainly associated with the fungal species Colletotrichum truncatum. Knowledge of the genetic structure of plant pathogen populations can be used to infer their life histories and the evolutionary processes that shape populations in the agroecosystems, which can help to implement effective disease management strategies. However, the genetic structure of C. truncatum populations associated with soybean remains unknown. We collected C. truncatum isolates from 10 sites representing two of main areas of soybean producing in Brazil and used microsatellite markers and whole-genome sequencing to investigate the population biology and evolutionary history of this important pathogen. The multilocus microsatellite typing of 237 isolates revealed high gene and haplotypic diversity within populations, as well low genetic differentiation and sharing of multilocus haplotypes among populations and regions. In addition, three distinct genetic clusters were detected, coexisting in syntopy in the soybean fields, without evidence of admixture between them. Such finding suggesting that Brazilian C. truncatum populations resulted from at least three founder events, which led to three genetic lineages that spread throughout the country. However, the genetic makeup of these lineages remains unknow, and their extreme geographic proximity raises the question of the maintenance of their genetic integrity in the face of admixture. In order to gain insights into the evolutionary history of C. truncatum lineages and to investigate in more details the possibility of a lack of genetic exchanges between them, we employed a population genomic approach. For that, we produced a draft genome sequence of a typical strain of the species associated with soybean anthracnose, which was used as the reference genome. Eighteen representative C. truncatum isolates from the three lineages were submitted to whole genome sequencing, aligned against the reference genome, and variants were identified. Our population genomic analyzes revealed that the genetic structure of C. truncatum pathogen causing soybean anthracnose is formed by three deeply divergent lineages with levels of genetic diversity consistent with repeated introduction events for each lineage. We also found evidence for sexual recombination within and between lineages, with multiples isolates displaying signatures of admixture. Our findings support a scenario in which the three lineages initially diverged in allopatry before experiencing hybridization following secondary contact. Monitoring of the pathogen\'s diversity over time is needed to reveal whether these lineages maintain or fuse, which can impact the disease control methods currently employed.